2008
DOI: 10.1063/1.2921972
|View full text |Cite
|
Sign up to set email alerts
|

Defects and transport in complex oxide thin films

Abstract: Epitaxial oxide thin films are at the heart of new “oxide electronic” applications, such as excitonic ultraviolet light-emitting diodes and resistive switching memories. Complex oxide films are often grown by pulsed laser deposition (PLD) because the technique is believed to be material agnostic. Here, we show that one of the fundamental premises used to justify the use of PLD, that material is transferred from an ablation target to the film without stoichiometry deviations, is incorrect even when no volatile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
275
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(314 citation statements)
references
References 27 publications
34
275
4
1
Order By: Relevance
“…The image shows that the film includes local and random structural changes, which might derive from randomly distributed RP type lattice displacements caused by the insertion of an extra SrO layer because the overall composition of the film is Sr-excess (Sr/(Sr+Ti) = 58.3 at.%). Such randomly distributed RP type defects are also reported by Ohnishi et al 25 for the epitaxial grown SrTiO 3 thin film with a Srexcess composition. As described above, the Sr-Ti-O thin film diffraction peak is observed at a lower angle than that of the SrTiO 3 single crystal, which suggests that the insertion of an extra SrO layer occurs at least along the out-of-plane (c-axis) direction.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The image shows that the film includes local and random structural changes, which might derive from randomly distributed RP type lattice displacements caused by the insertion of an extra SrO layer because the overall composition of the film is Sr-excess (Sr/(Sr+Ti) = 58.3 at.%). Such randomly distributed RP type defects are also reported by Ohnishi et al 25 for the epitaxial grown SrTiO 3 thin film with a Srexcess composition. As described above, the Sr-Ti-O thin film diffraction peak is observed at a lower angle than that of the SrTiO 3 single crystal, which suggests that the insertion of an extra SrO layer occurs at least along the out-of-plane (c-axis) direction.…”
Section: Resultssupporting
confidence: 53%
“…However, for the film with a Sr-excess composition (Sr/(Sr+Ti) = 58.3 at.%), a considerable increase of Δc ( = 0.0073 nm) was observed, which suggests that the insertion of an additional SrO layer is enhanced by the application of the magnetic field during deposition. In this figure, the relation between Δc and composition estimated by Ohnishi et al 25 for RP (SrTiO 3 ) x -SrO phases when treated as pseudocubic cells is also shown. In their estimation, Δc was calculated under the assumption that the insertion of an extra SrO layer occurs only along the out-of-plane (c-axis) direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the film is not stoichiometric, regardless of Sr rich or deficient, a diffraction peak from the film at a smaller angle than the substrate peak is seen, indicating a c-axis lattice expansion well established for homoepitaxial off-stoichiometric SrTiO 3 . 8,9 The c lattice constant vs. x is plotted for the films in Fig. 2c.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, conventional PLD using a compound target often results in cation off-stoichiometry in the films. 9,10 In this paper we present an approach that combines the strengths of reactive MBE and PLD: atomic layer-by-layer laser MBE (ALL-Laser MBE) using separate oxide targets. Ablating alternately the targets of constituent oxides, for example SrO and TiO 2 , a SrTiO 3 film can be grown one atomic layer at a time.…”
Section: Introductionmentioning
confidence: 99%